Uncommon cause of upper gastrointestinal bleeding: 30 mm duodenal polyp (brunnerian adenoma). Endoscopic treatment - Piazze, Alvaro; Bak, Miny; Mescia, Carlos; Laxalt, Victor (Revista Cirugía del Uruguay, 1997)
The authors present a case of upper digestive hemorrhage whose etiology was finally determined to be a voluminous Brunner's adenoma in the firs portion of the duodenum which was successfuly treated by means of endoscopical polypectomy. Authors emphasize the infrequency of this pathology. Endoscopical biopsies can be insufficient far definitive histological diagnosis.